Species Composition of Phytoplankton in the Gastrointestinal Tract of Hard Clam (Meretrix meretrix) in the Coastal Area of Laem Phak Bia: The King's Royally Initiated Laem Phak Bia Environmental Research and Development Project, Phetchaburi Province - ขาวหิต, เสถียรพงษ์; จันทร์แก้ว, เกษม; อิงคพัฒนากุล, วศิน; ผิวนลิ , อรอนงค์; บุตรสันติ์, อนุกรณ์ (KKU Science Journal, 2015)
Species composition of phytoplankton in the gastrointestinal tract of Meretrix meretrix was examined. Meretrix meretrix were collected from the coastal area of Laem Phak Bia, The King's Royally Initiated Laem Phak Bia Environmental Research and Development Project, Phetchaburi Province during May, 2012 to April, 2013. Species composition of phytoplankton was dominant by Coscinodiscus sp. (58.88%), followed by Cyclotella sp. (30.25%), Oscillatoria sp. (3.91%), Protoperidinium sp. (1.74%), Paralia sulcata (1.52%), Thalassiosira sp. (1.51%), Synedra sp. (1.30%) and Skeletonema sp. (0.88%) respectively of there, only Coscinodiscus sp. was found incomplete cell (39.72%).